Mongrelisation - Chasi, Colin, (Africana Philosophy ;, 2026)
Mongrelisation is a critical re-interpretation of why diversity and inclusion matter. It is a corrective that grants dignity and worth to those the 'mongrel' epithet is set to insult. Drawing on African moral traditions of Ubuntu and Maat, it contends that mongrelity-the reality that we are products of mixing and crossing-is too central in our histories, biologies, ecologies, and cultures not to be carefully humanised. The figure of the mongrel that it puts forward is akin to the hybrid, Creole, and coyote. This book includes cosmopolitan, mestizo, and Afropolitan perspectives.